Near-adult height in male kidney transplant recipients started on growth hormone treatment in late puberty - Gil, Silvia (2018)
Background: Growth retardation and its impact on adult height is considered to be one of the most common complications in patients with chronic kidney disease (CKD). Treatment with recombinant human growth hormone (rhGH) has been effective in improving growth in kidney transplantation (KTx) patients, but little data are available on adult height in patients who began rhGh treatment in late puberty. Methods: Near-adult height was evaluated in 13 KTx patients treated with rhGH [growth hormone group (GHGr); dose 9.33 mg/m2 per week] for a period of at least 18 months. At initiation of rhGH treatment, testicular volume was >8 ml and serum testosterone was >1 ng/ml compared with the control group (CGr) of ten KTx patients who did not receive rHGH. All subjects were of similar chronological age and bone age and had similar creatinine clearance (CrCl) levels, cumulative corticoid dose, height standard deviation score (SDS), target height SDS, and target height:initial height at the beginning of the study. Results: Near-adult height was significantly greater in the GHGr than in the CGr (−1.8 ± 0.8 vs. −2.9 ± 1.1; p = 0.018). The difference between initial height and near-adult height in the GHGr revealed a significant height gain (initial height −3.1 ± 1.1; near-adult height −1.8 ± 0.8 SDS, respectively; delta 1.2 ± 0.3; p = 0.021). The CrCl level was not significantly different between the GHGr and CGr at either at study initiation or when attaining near-adult height (p = 0.74 and p = 0.23, respectively). Conclusions: Treatment with rhGH was effective in improving adult height in KTx patients who began treatment in late puberty, without any effect on renal function.